2014
DOI: 10.3109/19396368.2014.949905
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol administration causes expression of calprotectin and RAGE altering the distribution of zinc ions in mouse testis

Abstract: Several studies reported that chronic alcohol consumption alters the intestinal mucosa barrier, and subsequent entrance of endotoxins into the bloodstream. In many tissues endotoxin exposure causes the expression of calprotectin (CP) and the receptor for advanced glycation -end products (RAGE). In this study we investigated whether chronic alcohol administration causes expression of CP and RAGE in mouse testis. The distribution of free and loosely bound Zn 2+ ) in the testicular tissues was also evaluated. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Acetaldehyde can form AA-DNA adducts in the brain and in peripheral blood leukocytes of people with AUD since ethanol, acetaldehyde, and lipid aldehydes such as MDA and 4-HNE can inhibit DNA repair enzymes 53 . The dual [251][252][253][254][255] Erythrocytes AA adducts ↑ correlated with FASD 257,258 Testis RAGE overexpression ↑ oxidative stress and inflammation↑ testis dysfunction and degeneration 253,[259][260][261] ↑ increase/activate, ↓ decrease/inactivate. mechanisms of simultaneously elevated AA-DNA adducts and suppressed DNA repair systems following alcohol intake may contribute to genetic instability and DNA mutations, promoting neurological pathologies 192,197,198 .…”
Section: Age-alcohol-adduct Formations (Fig 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetaldehyde can form AA-DNA adducts in the brain and in peripheral blood leukocytes of people with AUD since ethanol, acetaldehyde, and lipid aldehydes such as MDA and 4-HNE can inhibit DNA repair enzymes 53 . The dual [251][252][253][254][255] Erythrocytes AA adducts ↑ correlated with FASD 257,258 Testis RAGE overexpression ↑ oxidative stress and inflammation↑ testis dysfunction and degeneration 253,[259][260][261] ↑ increase/activate, ↓ decrease/inactivate. mechanisms of simultaneously elevated AA-DNA adducts and suppressed DNA repair systems following alcohol intake may contribute to genetic instability and DNA mutations, promoting neurological pathologies 192,197,198 .…”
Section: Age-alcohol-adduct Formations (Fig 1)mentioning
confidence: 99%
“…Alcohol intake can induce RAGE overexpression in the testis, whereby RAGE is localized in the interstitial cells and the basal compartment of the seminiferous tubules. Prolonged ethanol exposure stimulates RAGE activation to produce oxidative stress and inflammatory mediators, leading to testicular dysfunction and degeneration 259 . CYP2E1 and ALDH2 are also expressed in the testis 253,260,261 .…”
Section: Other Organsmentioning
confidence: 99%
“…It was proven that the consumption of ethanol excessively caused a decrease in the diameter, degeneration of sperm cells and germ cells, and the thinning of seminiferous tubules. It was indicated that alcohol damage happens due to the testicular interstitial cells and seminiferous tubules, especially the peritubular wall of the latter (Giannessi et al, 2015). It was reported that excessive alcohol intake resulted in testicular atrophy and gonadal failure.…”
Section: Discussionmentioning
confidence: 99%